Pengembangan media pembelajaran berbasis scratch dengan model problem based learning untuk meningkatkan kemampuan koneksi matematis siswa SMK pada materi barisan dan deret aritmetika - Amelia Putri Hasanah; Euis Eti Rohaeti; Eka Senjayawati (IKIP Siliwangi, 2026)
This study aims to developing Scratch-based learning media using the problem-based learning model to improve vocational high school students’ mathematical connection skills in the topic of Arithmetic Sequences and Series. The research method employed the Borg and Gall development model. The research subjects were 10th-grade students at a vocational high school in Bandung Regency. Data were collected through interviews, questionnaires, and a test instrument assessing mathematical connection skills, which were analyzed using Microsoft Excel and SPSS. The results indicated that the learning media were highly suitable,(88,47% from media experts and 92,69% from content experts). Furthermore, the media proved effective in improving mathematical connection skills, as evidenced by the high average post-test score of the experimental class (15.31) compared to the control class’s average score of 8.00. The experimental class’s N-Gain score was 0.71, classified as high, while the control class’s N-Gain score was 0.29, classified as low. The results of the one-sided Mann-Whitney test yielded a significance value of 0.000, leading to the conclusion that Scratch-based media is effective in improving mathematical connection skills.